2020
DOI: 10.1007/s12028-020-01111-1
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous Monitoring of Cerebral Autoregulation in Children Supported by Extracorporeal Membrane Oxygenation: A Pilot Study

Abstract: ObjectiveCerebral Autoregulation (CA) impairment may pose a risk factor for neurological complications among children supported by Extra-Corporeal Membrane Oxygenation (ECMO). Our first objective was to investigate the feasibility of CA continuous monitoring during ECMO treatment and to describe its evolution over time. The second objective was to analyze the association between CA impairment and neurological outcome. DesignObservational prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Although NIRS has been previously used as surrogate of cerebral blood flow in the dynamic measurement of autoregulation ( 15 , 16 ), its use is importantly limited by the fact that it takes into account both arterial and venous cerebral compartments, which do not take part in the same way for CBF regulation. Moreover, it has been mainly used in the paediatric population ( 15 , 16 ), and data on patients with COVID-19 are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although NIRS has been previously used as surrogate of cerebral blood flow in the dynamic measurement of autoregulation ( 15 , 16 ), its use is importantly limited by the fact that it takes into account both arterial and venous cerebral compartments, which do not take part in the same way for CBF regulation. Moreover, it has been mainly used in the paediatric population ( 15 , 16 ), and data on patients with COVID-19 are lacking.…”
Section: Discussionmentioning
confidence: 99%
“… 435 Optical oxygen delivery and autoregulation metrics may also individualize extracorporeal perfusion management. 432 , 433 , 438 441 In a related vein, modifications in diffuse optical hardware have accelerated the use of NIRS and DCS to monitor local spinal cord hemodynamics intraoperatively. This approach has been tested in ovine 442 444 and porcine 445 , 446 models so far, showing the feasibility and safety of using optical spectroscopy to monitor different sites of the spinal cord and identify early ischemia that can result in paralysis and paraparesis.…”
Section: Clinical Applications Of Optical Spectroscopy and Imagingmentioning
confidence: 99%
“…The right cerebral blood flow decreased during ECMO and was more susceptible to the interference of autoregulatory function, which seemed to explain the susceptibility to ANI in the right cerebral hemisphere. Additional studies showed that decreased cerebral oxygenation was associated with adverse short-term neurological outcomes and death (50)(51)(52)(53). In addition, a high rScO2 (>80%) was a protective factor that might predict a lower in-hospital mortality (54).…”
Section: Assessment Of Cerebral Oxygenationmentioning
confidence: 99%